(3GdJHUQI aj Yde GdgjFIs - (3CHh eMeO YHO GdLHGQ Hf YHO GdLHGQ Hf eMeO GdKGHJj GdNQbj,J (B553 (3g` s ((3MUf cdjHI s)
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hHYO , aEf GdYdeGA hGdMceGA cGfhG bHd ReGffG gPG eJhaQjf Ydi LejY GdYdhe hGdBf abO fGeJ Shb GdYde hHGQJ hCdaJ gPG GdcJGH ai Yde GdgjFI s
(3BNQgG (B:s
(3hGdefLehf jbSehf cd SGYI ef GdSGYGJ HSJjf bSekG, cd bSe ObjbI ; Ydi eG LQJ YGOJge aj bSeI GdHQhL hCLRGFgG HGdCLRGA GdSJjfjI adfNJe GdcJGH EPG CJjfG HGdehYhO Ydi MSH GdebOhQ hGdhGgH GdYbd GdMeO HdG fgGjI s
(3HgG LOGhd hQShe gfOSjI hadcjIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3Gdadcs